Family Economical Strategy and The Nutrition Fulfillment for Children Under Five: Improving Community Understanding - Irena Larashati; Sana Sholihah; Imelda Megawati; Arsylia Khoirunnisa Azzahra; Hamdan An Naisaburi; Merry Pramashela (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
As the next generation of the nation, toddlers need healthy food for optimal growth and development, as well as to reduce the risk of developing chronic diseases as adults. However, there are several things that prevent toddlers from getting balanced nutrition. One of them is low economic problems, lack of supporting facilities, and lack of public awareness of the fulfillment of nutrition in toddlers. The purpose of this program is to increase public awareness of toddler health as well as family economic management by providing counseling on how to make nutritious food for toddlers. In addition, this program also seeks to optimize the ability of related support systems, namely the role of posyandu, as a community empowerment function. The service method used is Participatory Action Research (PAR) with five main steps, namely identifying partners and analyzing needs, counseling on the fulfillment of toddler nutrition and cooking demonstrations, mentoring and monitoring, providing raw materials and equipment, as well as evaluation and further development. The output of community service activities is an increase in community understanding, implementation of raw material management, providing education on healthy food consumption habits. In addition, the results of this service are also the material for published articles. Based on the community service activities carried out, the understanding of the community shown by the understanding of the mothers increased based on the comparison of the results of the pre and post tests conducted. The desire to implement knowledge from the counseling results is also quite high. Education related to healthy food habits is also carried out during counseling and other educational media.